Efficacy of Different Insecticides in Controlling Pollen Beetle (Meligetes aeneus F.) in Rapeseed Crop (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Since pollen beetle, M. aeneus, is usually controlled by insecticides, the efficacy of several compounds with different modes of action against adult beetles was studied in a three-year field study. The selected insecticides were: three pyrethroids (lambda-cyhalothrin, alpha-cypermethrin and bifenthrin), an oganophosphate (pirimiphos-methyl), a combination of an organophosphate and a pyrethroid (chlorpyrifos + cypermethrin) and a neonicotinoid (thiacloprid). The insecticides were applied at label rates to winter rapeseed crops at the moment of visible but still closed flower buds (BBCH 55-57). In all experiments, the efficacy of pyrethroids and the organophosphate ranged from 90-100%, while the efficacy of the neonicotinoid was 85-95%. Therefore, they can be recommended for control of pollen beetle in Serbia.
Keywords: Mode of action; Insecticides; Pollen beetle